vì (x-2016)2 và (y+2017)2 đều lớn hơn hoặc = 0
=> (x-2016)2 = 0
=> x = 2016
=> (y+2017)2 = 0
=> y = -2017
mik nha chế
( x - 2016 )2 + ( y + 2017 )2 = 0
=> ( x - 2016 )2 = 0 và ( y + 2017 )2 = 0
+) ( x - 2016 )2 = 0
=> x - 2016 = 0
=> x = 2016
+) ( y + 2017 )2 = 0
=> y + 2017 = 0
=> y = -2017
Vậy x = 2016, y = -2017
Do (x-2016)^2 luôn lớn hơn hoặc bằng 0 và (y+2017) cũng luôn lớn hơn hoặc bằng 0
Nên để thỏa mãn (x-2016)^2+(y+2017)=0 thì x-2016=0,y+2017=0
suy ra x=2016,y=-2017
tổng x+y=2016-2017=-1